(untitled) (American Journal of Islam and Society, 2009)
Throughout Antiquity, the Middle Ages, and our current era, the Indian Ocean has been the economic backbone of an interconnected global community. This inter-territorial commerce, which feeds a vast network of merchants from the western Mediterranean to the South China Sea, probably constitutes the single most important cultural milieu in human history. While many existing studies highlight these networks’ significance and even a subdiscipline in academia focuses on the “Indian Ocean,” some significant components of the interlinking system are missing. A particularly difficult problem is the shortage of primary material from the system’s earlier periods, especially prior to the arrival of the Portuguese and the Dutch. The present volume, which is comprised of annotated and translated letters of various eleventh- and twelfth-centuryArab Jewish traders who interacted within this larger Indian Ocean complex, provides perhaps the most foundational source to understand the economic activities, communal organization, family life, and material civilization of the medieval world’s Arabicspeaking Jews. Indeed, with patience and a creative imagination, India Traders of the Middle Ages could lay the foundation for taking this subdiscipline in new directions ...